Krüppel-like factor 4 blocks tumor cell proliferation and promotes drug resistance in multiple myeloma - Schoenhals, Matthieu; Kassambara, Alboukadel; Veyrune, Jean-Luc; Moreaux, Jerome; Goldschmidt, Hartmut; Hose, Dirk; Klein, Bernard (Haematologica, the hematology journal, 2013)
Krüppel-like factor 4 is a transcription factor with anti-proliferative effects in differentiated cells, but with the ability to reprogram adult cells into cell-cycling pluripotent cells. In cancer, Krüppel-like factor 4 acts as either an anti-oncogene or an oncogene. We analyzed Krüppel-like factor 4 gene expression in multiple myeloma using Affymetrix microarrays. We generated conditionally expressing Krüppel-like factor 4 myeloma cell lines to investigate the function of this gene in myeloma biology. Krüppel-like factor 4 gene expression is high in normal plasma cells, but reduced in primary multiple myeloma cells from two-thirds of patients. It is not expressed by any human myeloma cell line due to promoter methylation. Conditional expression of Krüppel-like factor 4 led to complete cell cycle blockade, mainly in G1 phase, with no major apoptosis. This blockade was associated with induction of p21Cip1 and p27Kip1 in cell lines with an intact p53 pathway, and of p27Kip1 only in those with an impaired p53 pathway. Krüppel-like factor 4 is highly expressed in the poor prognostic MS group with t(4;14) translocation and in the good prognostic CD-1 group with t(11;14) or t(6;14). The apparent contradiction of cell cycle inhibitor Krüppel-like factor 4 expression in patients with poor prognosis could be reconciled since its expression increased the resistance of myeloma cell lines to melphalan. In conclusion, we describe for the first time that Krüppel-like factor 4 could play a critical role in controlling the cell cycle and resistance to alkylating agents in multiple myeloma cells.
Gesehen am 15.07.2021
DOI funktioniert nicht